Gender of Siblings and Choice of College Major - Massimo Anelli; Giovanni Peri (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this study we analyze whether the gender composition of siblings within a family affects the choice of College Major. The question is whether a family environment that is more gender-homogeneous encourages academic choices that are less gender stereotyped. We use the last name and the exact family address contained in a unique dataset covering 30,000 Italian students graduated from high school between 1985 and 2005 to identify siblings. We follow the academic career of these individuals from high school to college graduation. We find that mixed gender siblings within a family tend to choose college majors following a stereotypical gender specialization. Namely, males have higher probability of choosing male dominated majors such as Engineering and women higher probability of choosing female dominated majors such as Humanities. Same-gender siblings, on the other hand, have higher probability of making non-gender stereotyped choices. This college major choice is not driven by the choice of high school academic curriculum, which appears to be mainly function of geographical proximity to schools.
Keywords: I23; I24; J12; J16; 330; gender; choice of college major; family structure